Hubungan Riwayat Imunisasi Dasar Dan Riwayat Infeksi Dengan Kejadian Stunting Pada Balita: Tinjauan Pustaka - Reizki Arsyad; Sutarto .; Novita Caolia (CV. Jasa Sukses Abadi, 2023)
Stunting is a condition of growth failure in children caused by malnutrition from the womb until the age of 2 years, and the child is considered too short when compared to normal children of his age. The World Health Organization (WHO) noted that in 2018, there were 21.9% of stunting toddlers in the world and 14.9% in Southeast Asia. Meanwhile, in Indonesia, it was recorded that in 2018, there were at least 30.8% of toddlers who experienced stunting. Many factors can cause stunting in toddlers, for example, such as toddler nutritional intake, parental income, basic immunization history, infectious diseases, early initiation of breastfeeding, exclusive breastfeeding, low birth weight, and early marriage. Basic immunization that is not fulfilled completely will cause toddlers to experience infectious diseases and cause their appetites to decrease so that their nutritional intake is not sufficient, which has an impact on stunting.